HUBUNGAN ANTARA KELIMPAHAN KISTA DINOPHYCEAE DENGAN PARAMETER FISIKAKIMIA PERAIRAN DI TELUK JAKARTA - Yuliana Yuliana (Jurnal Perikanan Universitas Gadjah Mada, 2014)
Phytoplankton mainly Dinoﬂ agellata group on sexual reproductive phase will form a cyst when water conditions worsened. Cyst that was in the column will settle to the bottom, forming sediments that abundance is closely related to the events that occurred at an earlier time. This study aims to examine the relationship between abundance of Dinophyceae cysts with physico-chemical parameters of waters in the Jakarta Bay. Research conducted in the Jakarta Bay in August 2009, September 2009, November 2009, January 2010, March 2010 and May 2010 with the number of the location of sediment sampling are 9 stations. Sediment sample were taken using a corer which the pipe made of elliptical. Sample handling is done by the separation between the sediments and cysts which is covering the sifting process, then performed panning. The water samples that has been separated by sediment stored in sample bottles and preserved by using formalin 4%, then identiﬁ ed using a microscope. The results showed that the physico-chemical parameters of waters were the temperature: 25,00-31,80oC, salinity: 28.00 to 33.00, current: 9.81 to 30.51 cm.det-1, acidity : 6.58 to 8.63, brightness: 1.25 to 4.50 m, depth: 4.00 to 7.00 m, nitrates: 0.0072 to 0.0982 mg.l-1, and orthophosphate: 0, 0114 to 0.4076 mg.l-1. Dinophyceae cyst abundance during the study ranged from 51-8081 kista.cm-3. Meanwhile, the composition of the types of cysts Dinophyceae consists of 8 (eight) genus. The results of Pearson’s correlation analysis showed that the current value of Pearson’s correlation was 0.233 provides the most profound and positive correlation to the presence of cysts Dinophyceae during the study.